Metabolic patterns reveal enhanced anammox activity at low nitrogen conditions in the integrated I‐ABR. (25th May 2021) - Pan, Juejun; Huo, Tangran; Yang, Hui; Li, Zhenshan; Chen, Liming; Niu, Zhao; Ni, Shouqing; Liu, Sitong
Abstract: Substrate concentrations greatly influence bacterial growth and metabolism. However, optimal nitrogen concentrations for anammox bacteria in nitrogen‐limited environments remain unclear. Here, we observed enhanced nitrogen metabolism and anabolism of anammox bacteria at low nitrogen conditions. Efficient nitrogen removal was achieved at ammonium and nitrite influent concentration of 30 mg/L under HRT of 1 hr, with an average nitrogen removal rate (NRR) of 0.73 kg N/(m 3 ·day) in I‐ABR composed of four compartments. The highest anammox activity of 6.25 mmol N/ (gVSS·hr) was observed in the fourth compartment (C4) with the lowest substrate levels (ammonium and nitrite of 11.6 mg/L and 7 mg/L). This could be resulted from the highest expression level of genes involved in nitrogen metabolism in C4, which was 1.49–1.67 times higher than that in other compartments. Besides, the second compartment (C2) exhibited the most active anabolism at ammonium and nitrite of 17 mg/L and 13 mg/L, respectively, which contributed to the most active amino acid synthesis and thus the highest EPS (1.35 times higher) in C2. This enhanced amino acid auxotrophy between anammox bacteria with heterotrophs, and consequently, heterotrophs thrived and competed for nitrite. These results hint at the potential application of anammox process in micro‐polluted water. Practitioner points: High nitrogen removal and efficient biomass retention at low nitrogen concentrations under short HRT was achieved in I‐ABR. Optimal concentrations for anammox nitrogen removal and anabolism were discussed under low nitrogen concentrations. More active anabolism contributed to enhanced amino acid synthesis and thus higher EPS contents. Low substrate levels led to enhanced expression of genes involved in nitrogen metabolism and thus high anammox activity. Abstract : Schematic of the study keystone. High nitrogen removal and efficient biomass retention were achieved at ammonium and nitrite influent concentration of 30 mg/L under HRT of 1h in I‐ABR. The highest anammox activity was observed in the fourth compartment (C4) with the lowest substrate levels while the second compartment(C2) exhibited the most active anabolism.